Principles of Animal Locomotion - Alexander, R. McNeill (Book collections on Project MUSE., 2006)
This text provides an up-to-date overview of how animals run, walk, jump, crawl, swim, soar, hover, and fly. It covers all animals that power their movements with muscle, excluding only the tiny creatures that use cilia.